The relationship between transformational leadership, transactional leadership and innovative work behaviour in SMEs’ rubber and plastic product manufacturing companies - Hee, Kai Qi (2021)
This research examines the relationship between transformational leadership and transactional leadership towards innovative work behaviour. The research was conducted to analyse the influence of transformational leadership and transactional leadership towards innovative work behaviour among 162 employees who possess leader position in SMEs' rubber and plastic product manufacturing companies in Ipoh, Perak and Klang Valley Selangor. The data was analysed by using Statistical Package for the Social Science (SPSS) Version 26. Leader-Member Exchange Theory (LMX) was adopted to describe the possible association between independent variables and dependent variable to support the research framework. Based on Pearson's correlation analysis, the findings showed that transformational leadership and transactional leadership associate with innovative work behaviour. Next, multiple regression result showed that transformational leadership influences the most on innovative work behaviour compared to transactional leadership. The researcher showed several limitations when conducting this study and suggested several recommendations to enhance innovative work behaviour among leaders in SMEs' rubber and plastic product manufacturing companies.